Mental Health Impact of Mass Depopulation of Swine on Veterinarians During COVID-19 Infrastructure Breakdown - Baysinger, Angela; Kogan, Lori R. (Frontiers in Veterinary Science, 2022)
This study was designed to assess the mental health of swine veterinarians involved with mass depopulation events related to COVID-19 and compare them to swine veterinarians not involved in mass depopulation. Additionally, we assessed the well being, quality of life, psychological distress, burnout, and resilience in veterinarians who conducted depopulation events and the potential impact of depopulation methods on these factors. Finally, we identified coping methods utilized by swine veterinarians for improved well being. The study involved the distribution of an anonymous online survey, available December 2020 to January 2021, to swine veterinarians practicing in the United States. A total of 134 responses were analyzed. Stress related to the depopulation effort was predominantly an outcome of two factors: ethics of care (people and pigs) and perception of others (public, colleagues, family, friends, neighbors). Depopulation involvement was associated with burnout (p = 0.001). The depopulation method utilized significantly impacted depopulation distress (p = 0.007), perception of others (p < 0.001), and burnout (p < 0.001). Nearly one-third (29%) of all participants reported moderate levels of burnout. Based on these results, the call to action is to enhance the availability and visibility of existing mental health services and take necessary steps to destigmatize mental health. Additionally, it is critical to support the development of mental health programs for swine veterinarians through education, training, research, and transparent communication.